Effects of Rumination and Acceptance on Body Dissatisfaction in Binge Eating Disorder. (8th August 2014) - Svaldi, Jennifer; Naumann, Eva
Abstract Overvaluation of shape and weight and the corresponding body dissatisfaction are a maintenance factor for the psychopathology of binge eating disorder (BED). Evidence suggests potential benefits of various emotion regulation (ER) strategies in the modification of body dissatisfaction. Therefore, in the present study body dissatisfaction was experimentally induced in women with BED (n = 30) using model pictures. Then, participants were instructed to either ruminate on present emotions and thoughts or accept whatever thoughts and feelings come up. Body dissatisfaction and mood were assessed prior to, immediately after and 4 minutes after the induction. Main results reveal that ER strategies had no differential impact on body dissatisfaction. However, in the rumination condition mood significantly worsened over time. Overall, the results suggest that ER strategies have a limited impact on the experience of body dissatisfaction in BED. However, having an impact on mood, they may be important with regard to the maintenance of pathological eating behaviour in BED. Copyright © 2014 John Wiley & Sons, Ltd and Eating Disorders Association.